Safety and Outcomes of Overnight Discharge Following Elective Percutaneous Coronary Intervention at a Tertiary Cardiac Centre in Nepal - Sahi, Ravi; Simkhada, Rabindra; Neupane, Keshab Raj; Tamrakar, Rikesh; Yadav, Dharmanath; Timalsena, Birat Krishna; Adhikari, Suman (Nepalese Heart Journal, 2026)
Background and aims: Advances in percutaneous coronary intervention (PCI) have improved procedural safety, enabling consideration of shorter hospital stays after uncomplicated procedures. However, evidence supporting early discharge strategies in low- and middle-income countries remains scarce. This study evaluated the safety and feasibility of overnight discharge following elective PCI in a tertiary cardiac center in Nepal. Methods: In this prospective observational study, 375 consecutive patients undergoing uncomplicated elective PCI were enrolled. All patients were monitored overnight and discharged the following day if clinically stable. The primary outcome was the incidence of major adverse cardiovascular events (MACE) within 30 days. Results: The mean age of the study population was 59.4 ± 9.6 years, with males comprising 75.7% (n = 284). Transradial access was utilized in 85.6% (n = 321) of procedures. At 30-day follow-up, no major adverse cardiovascular events (MACE) or hospital readmissions were observed. Minor bleeding events (BARC 1–2) occurred in 62 patients (16.5%), while no major bleeding complications were recorded. Conclusions: Overnight discharge following uncomplicated elective PCI appears feasible with low observed event rates in carefully selected low-risk patients in a resource-limited setting.